Combinação social e construção de equipes: um estudo sobre os fatores relevantes para o processo de composição de equipes na educação executiva brasileira - Feitosa, Douglas de Lima (2016)
Team Composition is a recurring theme in different areas of knowledge. Researchers, practitioners and developers of information ystems (IS) are constantly seeking answers with regards to the steps and relevant variables of this process, which is considered complex. However, while some theoretical streams from organizational studies pursue the development of mathematical models, which reflect the relationship between team composition variables and team performance, emerging theories, such as Social Matching, add new elements to this discussion. Additionally, context-specific variables, like the ones found in Brazilian executive education, are also mentioned as having relevance for team building. Given the interest and variety of theoretical perspectives which address this phenomenon, this research sought to describe the teaching staff composition process and to identify the variables considered important on this process. An initial theoretical model was developed and applied considering multiple knowledge streams. Given the characteristics of the research question, exploratory and descriptive methodological approach was used, based on multiple case studies, carried out in four Brazilian higher education institutions which offer executive education courses. Data collection and data analysis were conducted considering methods proposed by Huberman and Miles (1983) and Yin (2010), com prising the use of a case study protocol, as well as the use of tables and charts, standardized in compliance with the proposed theoretical model. The results indicate mainly that: theories of social matching and education add elements which are relevant to understanding the team composition process; there are non-structured variables which are not considered in documents used to evaluate and to select professionals for teaching staff; and there are team composition variables which are only considered after the end of the first activity cycle. Based on empirical findings, the theoretical model was adjusted and displayed. Additional contributions, insights, limitations and proposals for future studies are presented in the conclusions chapter.